Comprehensive Analysis of LIN28A in Chinese Patients With Early Onset Parkinson’s Disease - Gu, Xiaojing; Hou, Yanbing; Chen, Yongping; Ou, Ruwei; Cao, Bei; Wei, Qianqian; Zhang, Lingyu; Song, Wei; Zhao, Bi; Wu, Ying; Shang, Huifang (Frontiers in Genetics, 2021)
A loss-of-function variant in Lin-28 Homolog A gene (LIN28A p.R192G, rs558060339) has been identified in two East Asian ancestry patients with early-onset PD (EOPD). Functional studies revealed that such variant could lead to developmental defects and PD-related phenotype, and the phenotypes could be rescued after correction of the variant. The aim of the study was to screen the variants of LIN28A in Chinese patients with EOPD. A total of 682 EOPD patients were sequenced with whole exome sequencing and the coding and flanking region of LIN28A were analyzed. We identified a rare coding variant p.P182L of LIN28A in a Chinese patient with EOPD. Moreover, we also found a 3’-UTR polymorphism (rs4659441) to be associated with an increased risk for PD. However, our rare variant burden analysis did not support a role for LIN28A as a major causal gene for PD.